Analysis of the Validity of Psycho-pedagogical Variable Constructs in Improving the Performance of Inclusive School Teachers in Indonesia - Siswandari, Vanda Estetika; Suharini, Erni; Mulyono, Sungkowo Edy; Prihatin, Titi (Universitas Negeri Semarang, 2025)
This study aims to analyze the construct validity of psycho-pedagogical variables consisting of pedagogical competence, organizational culture, self-efficacy, and spiritual intelligence in an effort to improve teacher performance in inclusive schools. The study was conducted with a quantitative approach using the SEM-PLS analysis technique. Data were obtained from 250 teachers who teach in inclusive schools in Semarang City. The results showed that all indicators in each construct had a loading factor value of > 0.7, Average Variance Extracted (AVE) > 0.5, and Composite Reliability (CR) > 0.7, indicating that all variables had good construct validity. These findings contribute to the development of measuring instruments in the context of inclusive education and provide an empirical basis for policy making to improve teacher quality.